Hannah Montana : Awesome Adventures - Friese, Kim; Series Created by Pryes, Michael ; Correll, Rich and O' Brien, Barry (New York Reader's Digest Children's Books)
Adaptation of two episodes from the popular television show, including "Lilly, Do You Want to Know a Secret" in which Miley tries to keep her identity as Hannah Montana a secret from Lilly, her best friend.
Include Color Illustrations
Keywords: Singers -- Montana, Hannah (Fictitious character)